IoT-based Intelligent System for Laboratory Facility Control with Blynk - Rakhmawati, Puji Utami; Rizdania, Rizdania; Muladi, Muhammad Nasikhul (Journal of Information System Research (JOSH), 2024)
This study presents the development of a smart laboratory using the Internet of Things (IoT) intelligent system technology to control electronic devices, especially air conditioners (AC). The AC in the laboratory is a device that consumes very high electrical power. Human resources personnel who use the laboratory often forget to turn off the devices after use. The problem is high electricity costs due to forgetting to switch off devices. This study solves this problem with an IoT-based intelligent system to control laboratory facilities by utilizing the Blynk App. Blynk is an Android-based open-source software that can connect with ESP32, so control can be done easily anywhere and anytime. In this study, a prototype IoT control system was developed that allows users to control and monitor equipment via the internet automatically. This study uses ESP32 technology, where an Arduino device is used as the receiver connected to Wi-Fi, and a microcontroller is used as an automatic control. ON/OFF control using 220v 30A relays as many as four pieces. Test results from this study showed that the device provides a response time of 1 second to respond to commands, and the four relays installed successfully controlled the devices.